2016
DOI: 10.1177/1203475416653734
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cure Rates in Onychomycosis

Abstract: To improve treatment success in onychomycosis, we suggest the following measures be followed: (1) onychomycosis must be correctly diagnosed, (2) the treatment regimen should be tailored to the individual patient, (3) the efficacy of antifungals must be maximized, and (4) recurrence must be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 153 publications
(152 reference statements)
0
38
0
3
Order By: Relevance
“…A 2013 systemic review of 11 population-based and 21 hospital-based studies showed that the mean prevalence of onychomycosis in North America and Europe was 4.3% (95% confidence interval: 1.9 to 6.8) in the population-based studies and 8.9% (95% confidence interval: 4.3 to 13.6) in the hospital-based studies [ 38 ]. There is evidence that the prevalence is rising, possibly because of longer life expectancy, use of occlusive modern footwear, increased prevalence of obesity, and increased urbanisation [ 17 , 39 , 40 ]. The condition is much more common in adults than in children and the prevalence increases with age [ 8 , 14 , 36 , 41 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…A 2013 systemic review of 11 population-based and 21 hospital-based studies showed that the mean prevalence of onychomycosis in North America and Europe was 4.3% (95% confidence interval: 1.9 to 6.8) in the population-based studies and 8.9% (95% confidence interval: 4.3 to 13.6) in the hospital-based studies [ 38 ]. There is evidence that the prevalence is rising, possibly because of longer life expectancy, use of occlusive modern footwear, increased prevalence of obesity, and increased urbanisation [ 17 , 39 , 40 ]. The condition is much more common in adults than in children and the prevalence increases with age [ 8 , 14 , 36 , 41 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Sin embargo, existen factores que predisponen a la recurrencia. Dentro de estos se encuentran: inmunosupresión, presencia de tiña pedis, historia familiar de OM, humedad, calzado oclusivo, higiene deficiente, trauma ungueal, tratamiento incorrecto de la infección original y baja adherencia al tratamiento 41 .…”
Section: Prevención De Recurrenciasunclassified
“…Se debe lavar el calzado con agua > 60°C por más de 45 minutos, opción disponible al utilizar máquinas lavadoras 40 . Mención especial merece el tratamiento de familiares con OM, dado a que serían la fuente de reinfección en un 86% de los casos 29,41 .…”
Section: Prevención De Recurrenciasunclassified
“…Combining onychomycosis treatment options can increase their efficacy and improve patient outcomes, possibly due to synergy, differing mechanisms of action and restricting the effect of fungal resistance [ 52 ]. In their 2017 review, Gupta and colleagues [ 52 ] summarised studies combining oral and/or topical drugs for onychomycosis, revealing that combination therapy is sometimes (though not always) more effective than monotherapy. Most studies combined oral terbinafine or itraconazole with topical amorolfine 5%, ciclopirox 8% or terbinafine.…”
Section: Combination Therapymentioning
confidence: 99%
“…Many combination therapies for onychomycosis are based on improving drug delivery to the infected nail via adjunct physical, mechanical or chemical treatments, including nail filing, nail trimming, debridement, chemical avulsion and the drilling of small holes into the nail plate (microporation) [ 52 ]. A promising emerging adjunct treatment is iontophoresis, which may be combined with topical therapies to improve their effectiveness.…”
Section: Combination Therapymentioning
confidence: 99%